1994
DOI: 10.1007/bf01972889
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular study of DiGeorge sequence

Abstract: DiGeorge sequence (DGS) is a developmental field defect of the third and fourth pharyngeal pouches. The cardinal features of the syndrome are hypo- or aplasia of the thymus and parathyroids, congenital heart defect of the conotruncal type and characteristic facial dysmorphism. Such a pattern of malformations has been associated with various conditions but it is now well established that most cases of DGS are due to haplo-insufficiency of the chromosome 22q11 region. We report here a series of 16 patients, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…DGA (in our study) and Opitz GBBB syndrome (McDonald-McGinn et al 1995) associated with CAF had the deletion of the 22q11.2 region Many of these defects are also seen in the Opitz GBBB (Opitz et al 1969a, b;McDonald-McGinn et al 1995) syndrome. This overlap of phenotype between previously distinct syndromes (Levy-Mozziconacci et al 1994;Nickel et al 1994;Burn et al 1995;Cormier-Daire et al 1995;Karayiorgou et al 1995) may reflect the result of haploinsufficiency of multiple genes located in 22q11.2. Therefore, we propose naming the four syndromes with a deletion of the 22q11.2 region, i.e., CAFS, VCFS, DGA, and Opitz GBBB, del22q11.2 syndrome (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…DGA (in our study) and Opitz GBBB syndrome (McDonald-McGinn et al 1995) associated with CAF had the deletion of the 22q11.2 region Many of these defects are also seen in the Opitz GBBB (Opitz et al 1969a, b;McDonald-McGinn et al 1995) syndrome. This overlap of phenotype between previously distinct syndromes (Levy-Mozziconacci et al 1994;Nickel et al 1994;Burn et al 1995;Cormier-Daire et al 1995;Karayiorgou et al 1995) may reflect the result of haploinsufficiency of multiple genes located in 22q11.2. Therefore, we propose naming the four syndromes with a deletion of the 22q11.2 region, i.e., CAFS, VCFS, DGA, and Opitz GBBB, del22q11.2 syndrome (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Since fluorescent in situ hybridization (FISH) was first used to detect 22q11.2 deletion [4], many large studies have been conducted investigating the associated cardiovascular anomalies in pediatric or adult patients [5-9]. Because of the strong correlation of 22q11.2 deletion with cardiac defects, many obstetricians recommend routine genetic screening for 22q11.2 deletion by FISH when heart defects are diagnosed on prenatal ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental disability has been identified in a proportion of these children. [1][2][3][4][5] Neurological sequelae are also well recognised following cardiac surgery, especially with major defects such as arch anomalies, prolonged cardiopulmonary bypass time, and after periods of low perfusion pressure. 6 7 Early reports of DGS in the cardiovascular literature either did not comment on neurological outcome 8 or simply indicated that neurodevelopmental sequelae are common.…”
mentioning
confidence: 99%